Genetic variability and character association studies in French bean (Phaseolus vulgaris) in Nilgiri hills of Tamil Nadu - NOOPUR, KOHIMA; JAWAHARLAL, M; PRANEETHA, S; KASHYAP, POONAM; SOMASUNDARAM, E (The Indian Journal of Agricultural Sciences, 2019)
In the present investigation, the genotypic and phenotypic coefficients of variation, heritability, correlation and path coefficient analysis were worked out for yield and its contributing characters of 77 French bean (Phaseolus vulgaris L) genotypes at Horticultural Research Station, TNAU, Udhagamandalam, Nilgiris,Tamil Nadu, India in 2018 with the objective of identifying desirable traits contributing to higher yield in French bean. Phenotypic coefficient of variation was slightly higher than genotypic coefficient of variation for all the characters suggesting the presence of environmental influence to some extent in the expression of these characters. High heritability along with high genetic advance as per cent of mean was observed for plant height, pods per plant and seed yield per plant indicating that these characters would be amenable for phenotypic selection. A considerable amount of genetic variability was observed among all the genotypes for all the characters under study. Genotypic coefficients variance and Phenotypic coefficients variance were highest for seed yield per plant followed by biological yield and number of pods per plant. High genetic advance coupled with high heritability were observed for plant height, days to 50% flowering, number of primary branches per plant, pod length, pod girth, seeds per pod, number of pods per plant, biological yield and seed yield per plant. Combined results of correlation coefficient and path analysis revealed that pods per plant, pod length, pod girth, biological yield and seed yield are major component traits for improvement of grain yield. The present findings could be useful in selecting superior genotypes in French bean breeding programmes.